Association of serum lipids with clinical outcome in acute ischaemic stroke: A systematic review and meta-analysis. (January 2019) - Deng, Qiwen; Li, Shuo; Zhang, Hanqing; Wang, Huan; Gu, Zhengtian; Zuo, Lei; Wang, Lvyue; Yan, Fuling
Highlights: The association between serum lipid and clinical outcomes in acute ischaemic stroke is assessed by enrolling 21 studies. Lacking of association between serum lipid and clinical outcomes in acute ischaemic stroke is suggested. The primary risk factors of stroke should be focused to improve secondary prevention for acute ischaemic stroke. Abstract: Serum lipid levels have been investigated as prognostic markers in patients with acute ischaemic stroke. However, these results remain inconsistent. This study aimed at assessing the association between serum lipid and clinical outcomes in acute ischaemic stroke. Relevant data were obtained from Cochrane Library, PubMed and Web of Science databases. The heterogeneity of pooled results was determined by the Cochran's Q test and Higgins I-squared statistic. The random-effect model was performed to calculate the pooled results if P H  < 0.05 for Q-test, otherwise the fixed-effect model was applied. The primary results were death, and the secondary were recurrence, dependency, mRS score ≥3, and early neurological deterioration. A total of 21 full-text studies was included in the present study. For primary results, the pooled results from 5 studies with 4119 patients showed that triglyceride (TG) was a significant predictor for death (OR = 0.65, 95%CI = 0.43–0.98, P H  = 0.028). The pooled data from 11 studies with 12, 486 patients for total cholesterol (TC), 4 studies with 7593 patients for low-density lipoprotein cholesterol (LDL-C), and 5 studies with 6933 patients for high-density lipoprotein cholesterol (HDL-C) suggested that TC (OR = 0.79, 95%CI = 0.56–1.13, P H  < 0.001), LDL-C (OR = 1.02, 95%CI = 0.66–1.57, P H  = 0.042), and HDL-C (OR = 1.18, 95%CI = 0.75–1.86, P H  = 0.003) were not associated with death in acute ischaemic stroke. For secondary results, the pooled results of 2 studies with 867 patients indicated that TG was positively associated with early neurological deterioration. This study suggested that serum TG was associated with death and early neurological deterioration in acute ischaemic stroke.